L’attivo bisogno di apprendere - Travaglini, Roberto (Studi sulla Formazione/Open Journal of Education, 2024)
The article explores how much current pedagogical theories rooted in John Dewey’s pragmatism give importance to biological motivations in the development of learning processes. Dewey identified four fundamental instincts in children (social impulse, instinct to make, instinct of investigation and art instinct), and was convinced that effective learning is achieved when children are guided by similar internal drives rather than by external stimuli. It is an approach that shifts the educational attention from the teacher to the child, enhancing his natural need to know through practical and creative activities. The motivation to learn has solid neurological foundations, supported by the most recent pedagogical-cognitivist and neo-cognitivist expressions in an anti-behaviorist function: Damasio argues that the idea of an “implicit consciousness”, present in vital processes and the primary basis of emotions and the highest cognitive abilities, is well-founded, and several authors align themselves on its theoretical perspective, including Piaget and Gardner, who have been able to integrate cognitive and biological sciences with educational theories, promoting an education capable of enhancing the interaction between innate predispositions and the socio-educational environment and, in line with Dewey’s activist orientation, promoting the idea – like Claparède’s law of need –, according to which the child’s mind is active and self-motivation is the real engine of any possible functional learning. La motivazione ad apprendere ha solide basi neurologiche, suffragate dalle più recenti espressioni pedagogico-cognitiviste e neo-cognitiviste in funzione anti-behaviorista: Damasio sostiene fondata l’idea di una "coscienza implicita" presente nei processi vitali e base primaria delle emozioni e delle più elevate capacità cognitive, sul cui prospetto teoretico si allineano diversi autori, tra cui Piaget e Gardner, i quali hanno saputo integrare le scienze cognitive e biologiche con le teorie educative, promuovendo un’educazione in grado di valorizzare l’interazione tra predisposizioni innate e ambiente socioeducativo e, in linea con l’orientamento attivista di Dewey, promuovendo l’idea – al pari della legge del bisogno di Claparède –, secondo cui la mente del bambino è attiva e l’automotivazione è il vero motore di ogni possibile apprendimento funzionale.